Achilles’ Heel of currently approved immune checkpoint inhibitors: immune related adverse events - Yan, Ting; Yu, Lun; Zhang, Jiwen; Chen, Yun; Fu, Yilan; Tang, Jingyi; Liao, Dehua (Frontiers in Immunology, 2024)
Immunotherapy has revolutionized the cancer treatment landscape by opening up novel avenues for intervention. As the use of immune checkpoint inhibitors (ICIs) has exponentially increased, so have immune-related adverse events (irAEs). The mechanism of irAEs may involve the direct damage caused by monoclonal antibodies and a sequence of immune responses triggered by T cell activation. Common side effects include dermatologic toxicity, endocrine toxicity, gastrointestinal toxicity, and hepatic toxicity. While relatively rare, neurotoxicity, cardiotoxicity, and pulmonary toxicity can be fatal. These toxicities pose a clinical dilemma regarding treatment discontinuation since they can result in severe complications and necessitate frequent hospitalization. Vigilant monitoring of irAEs is vital in clinical practice, and the principal therapeutic strategy entails the administration of oral or intravenous glucocorticoids (GSCs). It may be necessary to temporarily or permanently discontinue the use of ICIs in severe cases. Given that irAEs can impact multiple organs and require diverse treatment approaches, the involvement of a multidisciplinary team of experts is imperative. This review aims to comprehensively examine the pathogenesis, clinical manifestations, incidence, and treatment options for various irAEs.